Science Teachers' view on Sustainable Development in COVID-19 Pandemic Process - Hakan Türkmen (Journal of Science Learning, 2022)
This study examines what science teachers think about Sustainable Development and its' Goals, how they integrate SDGs into their science lessons, and how the covid-19 pandemic affects their thoughts about Sustainable Development. The study group was selected by convenience sampling from 51 middle schools in the central district of one of the big cities. The questionnaire, including five open-ended questions, was prepared and checked by two experts. After their feedback, it was re-corrected and then applied to the participants. It was conducted using the "Google Forms" application. Then, it was delivered to 165 teachers’ e-mail accounts. Answering the questionnaire takes approximately 10-15 minutes for each participant. One hundred five teachers answered the questionnaire. The content analysis method was used to analyze data. The results showed that teachers mainly described Sustainable Development with the goal of "Responsible Consumption and Production", "Decent Work and Economic Growth", and "Quality Education". Half of the teachers are still trying to integrate SD using traditional science subjects strategies. And generally focused on science subjects of matter cycles, environmental problems, biodiversity, fuels, and domestic waste and recycling. In this process, their problems are usually intense curriculum, insufficient time, and attitudes of school administration.